1977
DOI: 10.1111/j.1755-3768.1977.tb05682.x
|View full text |Cite
|
Sign up to set email alerts
|

CHANGES IN ULTRASTRUCTURE AND FUNCTION OF THE SHEEP PIGMENT EPITHELIUM AND RETINA INDUCED BY SODIUM IODATE1

Abstract: The present investigation shows that the membrane properties of the sheep pigment epithelial cells were very rapidly and severely affected by sodium iodate, whereas the effects concerning the neuroretina were delayed. The c-wave of the ERG was immediately abolished and replaced by a cornea-negative potential, but the a- and b-waves were preserved for about 80-100 min. Ultrastructurally the plasma membranes (particularly the basal plasma membrane) of the pigment epithelial cells were destroyed or less distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
30
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 36 publications
3
30
0
Order By: Relevance
“…Using rabbits, Clifton & Makous (1973) showed that the amplitudes of the a-and b-waves were not affected by NaIO, during the first 10 h after injection. Nilsson et al (1977) found decreased aand b-waves in sheep 100 min after NaIO, injection, although the sensory retina showed no or possibly very slight changes. We previously found decreased b-wave sensitivity, while the maximal response dramatically increased at 24 h after injection and lasted for several days.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Using rabbits, Clifton & Makous (1973) showed that the amplitudes of the a-and b-waves were not affected by NaIO, during the first 10 h after injection. Nilsson et al (1977) found decreased aand b-waves in sheep 100 min after NaIO, injection, although the sensory retina showed no or possibly very slight changes. We previously found decreased b-wave sensitivity, while the maximal response dramatically increased at 24 h after injection and lasted for several days.…”
Section: Discussionmentioning
confidence: 84%
“…Little information has been gathered on chan-ges of a-and b-waves of the ERG within the first hour of recording (Nilsson et al 1977).…”
mentioning
confidence: 99%
“…This may explain the transient increase in c-wave amplitude. Histopathological studies in sheep (Nilsson et al 1977) indicated that the earliest ultrastructural change after intravenous injection of 30 mg/kg of NaI03 was the destruction of the basal membrane and a less extent of the apical membrane of the pigment epithelium. Textorius & Welinder (198 1) reported that injection of 30 mg/kg of NaI03 increased the standing potential (SP), whereas injection of 40 mg/'kg NaI03 decreased it in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…C previously to abolish the c-wave (Noel1 1953(Noel1 , 1954(Noel1 , 1958(Noel1 , 1959(Noel1 , 1963Nilsson et al 1977). This observation was similar for both pigmented and albino rabbits, suggesting that pigmentation is not involved in the drug induced ERG changes.…”
mentioning
confidence: 85%
“…The morphology investigated by light microscopy 4 days later showed severe damage to the pigment epithelium, and Noell suggested that the c-wave of the 'on-ERG and the slow negative off-response were related phenomena and that they were generated mainly across the pigment epithelium. Later, Nilsson et al (1977a) observed severe ultrastructural damage to the pigment epithelium 2 h after the injection of NaIO3.…”
mentioning
confidence: 95%